Peran Quantum Learning Dalam Meningkatkan Secara Berlipat Target Belajar Bahasa Inggris Di SMA PGRI Cicurug - Amanah, Ima Muslimatul; Qomariyah, Siti; Sukandi, Andi (Faidatuna, 2023)
This study aims to describe the concept of quantum learning model, the steps of applying quantum learning model, the role of quantum learning in increasing multiple learning targets, and the advantages and disadvantages of quantum learning model. Quantum learning model is a learning model that can make students directly experience problems, find their own answers to problems and activities in accordance with the competencies to be achieved. The research method used is descriptive qualitative research method. Qualitative descriptive research method according to Kirk and Miller, defines that qualitative research is a certain tradition in social science that fundamentally relies on observations of humans both in their areas and in their terms. The research subjects were the English teacher, and the principal. The object of research is the students of class X-4 SMA PGRI Cicurug. The results showed that the success of quantum learning depends on the teacher's ability to understand the concept and implement quantum learning steps in their learning activities. Its application in English subjects is enough to show that there is an increase in student learning targets.